What are the barriers to scaling up health interventions in low and middle income countries? A qualitative study of academic leaders in implementation science - Yamey Gavin (BMC, 2012)
Abstract Background Most low and middle income countries (LMICs) are currently not on track to reach the health-related Millennium Development Goals (MDGs). One way to accelerate progress would be through the large-scale implementation of evidence-based health tools and interventions. This study aimed to: (a) explore the barriers that have impeded such scale-up in LMICs, and (b) lay out an "implementation research agenda"-a series of key research questions that need to be addressed in order to help overcome such barriers. Methods Interviews were conducted with fourteen key informants, all of whom are academic leaders in the field of implementation science, who were purposively selected for their expertise in scaling up in LMICs. Interviews were transcribed by hand and manually coded to look for emerging themes related to the two study aims. Barriers to scaling up, and unanswered research questions, were organized into six categories, representing different components of the scaling up process: attributes of the intervention; attributes of the implementers; scale-up approach; attributes of the adopting community; socio-political, fiscal, and cultural context; and research context. Results Factors impeding the success of scale-up that emerged from the key informant interviews, and which are areas for future investigation, include: complexity of the intervention and lack of technical consensus; limited human resource, leadership, management, and health systems capacity; poor application of proven diffusion techniques; lack of engagement of local implementers and of the adopting community; and inadequate integration of research into scale-up efforts. Conclusions Key steps in expanding the evidence base on implementation in LMICs include studying how to: simplify interventions; train "scale-up leaders" and health workers dedicated to scale-up; reach and engage communities; match the best delivery strategy to the specific health problem and context; and raise the low profile of implementation science.